(untitled) (Research, Society and Development, 2022)
The Present study aims to analyze the learning and mastery of educational technological tools by students and teachers in the remote teaching modality, during the new corona virus pandemic in a public school in Manaus-AM. Methodology: The descriptive research, with a quantitative approach, developed in the years 2020 and 2021, with a population of 1396 and a sample (N) 158 participants, divided between 103 students and 55 teachers from the Ruy Alencar State School, located in the city of Manaus -AM. A semi-structured electronic form containing open and closed questions was used in order to assess the socioeconomic and demographic issues of the actors. Results: Remote Teaching is being developed through online platforms such as Google Teams, Google Meet, Google Classroom and Zoom. With these technological educational resources, assessments, activities and interactive classes are carried out. Teachers are not satisfied with the functionality of the platforms, finding it difficult to explore these resources due to the fact that their academic training has not fully contemplated this knowledge, requiring greater professional qualification. The changes in the school routine brought work overload due to the intensity of the activities developed. As for students, most of them experience difficulties in using the aforementioned platforms, others do not have access to Technologies due to socioeconomic issues and a portion is dissatisfied with internet access. The precariousness of access to technological means due to socioeconomic issues and the difficulties inherent to internet signal providers has caused losses in the learning process, causing damage to student teaching and learning.